Manajemen Sumber Daya Manusia Komprehensif - Seftian Romli Ishaq, Muhammad (Muttaqien Publsihing, Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR.KH.EZ.Muttaqien Purwakarta, 2024)
Human Resource Management is part of management in general. Human resource management is essential in an organization, especially in educational institutions. Educational institutions with good human resource management are sure to be superior to various fields of academic institutions that need to manage their human resources properly.